PEMBINAAN IMAN ANAK DI PANTI ASUHAN EL-SHADDAI ABIGAIL PIAYU BERTEMA BERBAGI KASIH, MENYEBAR KEBAHAGIAAN - Purba, Gomgom; Vera Susanti Napitupulu (JURNAL BEATITUDES, 2025)
Children's faith development at the El-Shaddai Abigail Piayu Orphanage aims to provide a solid foundation in the formation of children's character and personality through the theme "Sharing Love, Spreading Happiness". This study uses a descriptive qualitative approach to explore the experiences and perceptions of children and caregivers in the context of faith development. The results of this development indicate that faith development programs that include spiritual and social activities not only increase children's self-confidence and happiness, but also strengthen their social relationships with peers and the community. Active involvement in love-sharing activities contributes to the development of empathy, tolerance, and sacrifice, which are essential in the growth of their faith. By focusing on structured faith development, this study highlights the need for collaboration between orphanages, churches, and communities to create an environment that supports children's spiritual development, as well as improving the quality of support for them in the future.